“Piston” mechanism in a time-dependent two-level model - MacChiavelli, A. O.; Civitarese, Enrique Osvaldo; Lenzi, S .M.; Liotta, R. J.; Bès, D. R. (American Physical Society, 2021)
Fil: MacChiavelli, A. O.. Lawrence Berkeley National Laboratory; Estados Unidos